Identifikasi Kandungan Bahan Tambahan Makanan Berbahaya dalam Pangan Jajanan Anak Sekolah di Kota Jayapura - Dianingsih, Nurlita; Abulais, Diana M.; Numberi, Yulindra M.; Panjaitan, Eunike M.; Sefa, Martha K. (Jurnal Biologi Papua, 2024)
Poor food safety in school children’s snacks (SCSS), characterized by the presence of hazardous additives like borax, formalin, and rhodamine B, poses significant risks to children's health, potentially leading to long-term health issues and developmental problems. This research aims to identify the presence of these dangerous substances in SCSS and determine which types of snacks pose the highest food safety risks. The study employed a simple random sampling method to collect popular snack samples frequently consumed by students in various areas of Jayapura. Qualitative testing for borax, formalin, and rhodamine B was carried out using test kits. The results revealed that several SCSS samples contained these harmful substances, with notable variability across different regions. The analysis identified specific types of snacks—such as meatballs, noodles, colorful beverages, and snacks—that failed to meet the expected food safety standards. The study concludes that hazardous food additives are still being used in the production and sale of SCSS in Jayapura City, posing significant health risks to children. Enhanced regulation and awareness initiatives are necessary to improve food safety in the region. Public health authorities are encouraged to implement stricter monitoring and provide targeted education to both vendors and consumers to reduce the prevalence of these unsafe practices. Key words: food safety; hazardous additives; Jayapura City; public health; school snacks.